Managing HBV in pregnancy. Prevention, prophylaxis, treatment and follow-up: position paper produced by Australian, UK and New Zealand key opinion leaders. Issue 2 (15th October 2015) - Visvanathan, Kumar; Dusheiko, Geoff; Giles, Michelle; Wong, May-Ling; Phung, Nghi; Walker, Susan; Le, Suong; Lim, Seng Gee; Gane, Ed; Ngu, Meng; Hardikar, Winita; Cowie, Ben; et al.
Abstract : Hepatitis B during pregnancy presents unique management issues for both the mother and fetus. These include the lack of a current cohesive strategy for treatment and follow-up of mothers and their babies; the uncertain risk of postpartum HBV flares; the lack of randomised trial data on the safety and efficacy of antiviral treatment in pregnancy; the lack of head-to-head studies comparing different antivirals in pregnancy; and the lack of epidemiologic information regarding infection across different populations globally. This position paper provides a comprehensive review of the management of women with HBV infection prior to conception, throughout each stage of pregnancy and postpartum, as well as recommendations and clinical approaches for the follow-up of children born to infected mothers, based on available evidence in the literature and recommendations from international experts. Prevention of perinatal transmission is an important component of global efforts to reduce the burden of chronic HBV since vertical transmission is responsible for most of the chronic infection worldwide.